Pengaruh Kepuasan Kerja dan Burnout terhadap Retensi Karyawan dengan Komitmen Organisasi sebagai Mediator pada Biro Pariwisata Religi di Bali - M. Faiz Ali Hidayat; Sholahuddin, Muhammad; Edy Purwo Saputro (ITB AAS Indonesia Surakarta, 2025)
This study aims to understand the effect of job satisfaction, burnout, and organizational commitment on employee retention at Hajj and Umrah travel agencies in Bali. The industry faces challenges in retaining employees due to the seasonal and intensive nature of the work. Using quantitative methods and SEM-PLS analysis, data from 150 respondents were analyzed to explore the relationships between variables. The results showed that job satisfaction has a significant influence on employee retention and organizational commitment, where satisfied employees tend to be more emotionally attached to the company and stay longer. On the other hand, burnout has a negative impact on affective commitment, but normative commitment still makes employees stay. Organizational commitment also acts as a mediator between job satisfaction and burnout on retention, strengthening employees' intention to remain in the company. Overall, this study provides important insights for the management of Hajj and Umrah travel agencies in designing strategies to increase job satisfaction, manage burnout, and strengthen employee commitment in order to retain a competent workforce.